Asset Recovery Of Corruption Proceeds Through Mutual Legal Assistance In Indonesia - Istiqomah, Milda; Milania A, Bunga Veronika (JURNAL LEGALITAS, 2026)
Corruption is a transnational crime that necessitates robust international cooperation to effectively trace and recover illicit proceeds. Despite ongoing anti-corruption efforts, a critical research gap persists regarding the normative and operational mismatch between Indonesia's current Mutual Legal Assistance (MLA) framework and the international asset recovery standards established in Chapter V of the United Nations Convention Against Corruption (UNCAC). Specifically, existing domestic regulations, including Law Number 1 of 2006 concerning Mutual Legal Assistance, lack comprehensive legal mechanisms to execute the forfeiture of corruption proceeds located outside Indonesian jurisdiction. To address this gap, this study aims to critically analyze the existing criminal law policies regarding the seizure of corruption assets through MLA and to formulate alternative legal arrangements to optimize asset recovery efforts in Indonesia. The research employs a normative juridical methodology, utilizing statutory and conceptual approaches, supported by grammatical, historical, and systematic interpretation techniques. The main findings reveal that the current domestic legal framework is fundamentally inadequate for addressing transnational asset forfeiture and fails to align with UNCAC standards. Consequently, the study advocates for the immediate enactment of the Asset Recovery Bill (Rancangan Undang-Undang tentang Perampasan Aset). This offers a significant theoretical contribution by strengthening the concept of Non-Conviction Based Forfeiture within the Indonesian legal system. Practically, it provides law enforcement agencies with a comprehensive legal foundation to effectively trace, seize, and manage illicit assets domestically and abroad, notably through the proposed establishment of a dedicated Asset Management Agency.